Studies on the biological effects of ozone: 11. Release of factors from human endothelial cells - Giuseppe Valacchi; Velio Bocci (Mediators of Inflammation)
Background: Empirical observations have shown that ozonated autohemotherapy markedly improves the symptoms of chronic limb ischemia (muscular pain at rest, intermittent claudication, etc ) in atherosclerotic patients, but mechanisms of action remain unclear.